Pengaruh Krisis Hipertensi pada Fase Akut Stroke terhadap Activity of Daily Living Pasien Pasca Stroke di RSUD Dr. Moewardi - Annisa Susilowati; Rivan Danuaji; Dhoni Akbar Ghozali (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Stroke is a problem for many countries in the world due to increase in line with the modernization and occurs most frequently in old age. Stroke incidence can cause functional acute brain disorder both focal and global which will end with disability or death. Crisis hypertensive is common in acute phase stroke patients who require proper treatment because it can aggravate brain damage and worsen outcome. Generally, post-stroke patients who can survive will be dependent on help of others in carrying out the activities of daily life. The decline in the independence of someone is one of functional outcome after stroke that needs more attention. Method: This study used observational analytic study design retrospective cohort approach in Outpatient Clinic of Neurology in RSUD Dr. Moewardi. Sampling was done by exhaustive sampling where all reasonable population is used as the study sample. Data collection techniques used questionnaires and interviews to respondents using the Barthel Index to measure Activity of Daily Living (ADL). This study analyzed the effect of crisis hypertensive on acute phase stroke to post-stroke ADL by controlling one of the confounding variable that is age. Data was analyzed using bivariate analysis that is chi square test and multivariate analysis with multiple logistic regression with SPSS 20.00. Result: Results of bivariate analysis showed that crisis hypertensive and age variables each significantly correlated to the post-stroke Activity of Daily Living. After controlling for confounding variables of age using multivariate analysis, found that the relationship of crisis hypertensive to post-stroke ADL remained significant (p = 0.006). The magnitude of the risk of poor ADL incident because of crisis hypertensive on acute phase stroke after considering age factor is 9.918 times (OR = 9,918). This means that post-stroke patients with crisis hypertensive in all age groups had 9.918 times greater risk for having poor ADL after stroke compared with patients without crisis hypertensive on acute phase stroke. Conclusion: Based on the results of this study concluded that crisis hypertensive on acute phase stroke has significant effect to post-stroke Activity of Daily Living in all age groups patients. Keyword: Stroke, Crisis hypertensive, Activity of Daily Living, post-stroke ADL